Mechanical properties of silicon carbide—in situ zirconium carbonitride composites. Issue 4 (3rd March 2019) - Malik, Rohit; Jang, Seung Hoon; Kim, Young‐Wook; Nishimura, Toshiyuki
Abstract: SiC–Zr2 CN composites were fabricated by conventional hot pressing from β‐SiC and ZrN powders with 2 vol% equimolar Y2 O3 –Sc2 O3 as a sintering additive. The effects of the ZrN addition on the room‐temperature (RT) mechanical properties and high‐temperature flexural strength of the SiC–Zr2 CN composites were investigated. The fracture toughness gradually increased from 4.2 ± 0.3 MPa·m 1/2 for monolithic SiC to 6.3 ± 0.2 MPa·m 1/2 for a SiC–20 vol% ZrN composite, whereas the RT flexural strength (546 ± 32 MPa for the monolithic SiC) reached its maximum of 644 ± 87 MPa for the SiC–10 vol% ZrN composite. The monolithic SiC had improved strength at 1200°C, whereas the SiC–Zr2 CN composites could not retain their RT strengths at 1200°C. The typical flexural strength values of the SiC–0, 10, and 20 vol% ZrN composites at 1200°C were 650 ± 53, 448 ± 31, and 386 ± 19 MPa, whereas their RT strength values were 546 ± 32, 644 ± 87, and 528 ± 117 MPa, respectively.